Taming the global financial cycle: What role for the global financial safety net?. (June 2019) - Scheubel, Beatrice; Stracca, Livio; Tille, Cédric
Abstract: An ongoing active debate considers the role of the Global Financial Cycle (GFC) in driving international capital flows - especially in emerging economies - as well as the policy options available to absorb their impact. We make two contributions to the debate. First, we rely on a structural measure of the GFC developed in a companion paper to identify episodes of large capital flows and currency crises driven by global conditions. Second, using both OLS and instrumental variables we evaluate whether the availability and actual use of elements of the Global Financial Safety Net (GFSN) can help emerging markets cushion the impact of these episodes. We find some evidence that potential access to IMF support can help countries. We also find that the use of IMF support and reserves cushions the impact of global shocks on GDP growth. This effect is quite heterogeneous across types of crises and across time, as it is mostly present during currency crises, and the benefits only occur with a delay.